Psychological Assistance Tool Model for Foreign Students with PTSD - Melnichuk, Melnichuk (International Journal of Psychosocial Rehabilitation, 2017)
Abstract: The present article represents an instrumental model for providing psychological support to foreign students with posttraumatic stress disorders caused by acquired traumatic experience and a trauma of migration. It shows the review of psycho-diagnostic tools that are applied in the proposed instrumental model, describes its characteristics and explains our choice.